2008
DOI: 10.1186/1471-2172-9-2
|View full text |Cite
|
Sign up to set email alerts
|

IgE alone promotes human lung mast cell survival through the autocrine production of IL-6

Abstract: Background: Mast cells play a key role in asthma and recent evidence indicates that their ongoing activation in this disease is mediated, in part, via IgE in the absence of antigen. In this study we have examined whether IgE alone enhances human lung mast cell (HLMC) survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…In addition to the classical view that IgE binding to FceRI on mast cells primes mast cells for activation by bivalent/multivalent antigens, it is now recognized that IgE binding to FceRI leads to activation of mast cells to release prosurvival cytokines that maintain viability of the cells (29)(30)(31). In the absence of external supporting cytokines, mast cells rapidly undergo apoptosis, which is suppressed by the addition of IgE.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the classical view that IgE binding to FceRI on mast cells primes mast cells for activation by bivalent/multivalent antigens, it is now recognized that IgE binding to FceRI leads to activation of mast cells to release prosurvival cytokines that maintain viability of the cells (29)(30)(31). In the absence of external supporting cytokines, mast cells rapidly undergo apoptosis, which is suppressed by the addition of IgE.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that IL-8 inhibited IL-4-induced IgE production and endogenous TNF-α and IL-6 are essential for IgE production in atopic patients [25,26]. In addition, IgE promotes the autocrine production of IL-6 in human lung mast cells [27]. Recently, a study showed that IgE-secreting cells differentiation and IgE production could be directly promoted by IL-17 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Mast cell survival and histamine content is increased in cultured mouse mast cells after monoclonal IgEs incubation [4,5,7]. Monomeric IgE binding to FcRI directly activates human lung mast cells leading to the release of inflammatory mediators and chemokines and the enhancement of mast cell survival [6,9]. We previously demonstrated that mast cells from sensitized animals increase the expression of syntaxin 4 and SNAP-23, two exocytotic proteins involved in the degranulation process [12].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the signaling from IgE alone in the absence of allergen is a result of FcRI aggregation, in the same way as FcRI cross-linking with allergen [6,8]. Synergistic signals are mediated by activation of FcRI and toll-like receptors to augment production of inflammatory cytokines [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation